SEP Montage Variability Comparison during Intraoperative Neurophysiologic Monitoring - Hanson, Christine; Lolis, Athena Maria; Beric, Aleksandar (Frontiers in Neurology, 2016)
Intraoperative monitoring is performed to provide real time assessment of the neural structures that can be at risk during spinal surgery. Somatosensory evoked potentials (SEPs) are the most commonly used modality for intraoperative monitoring. SEP stability can be affected by many factors during the surgery. This study is a prospective review of SEP recordings obtained during intraoperative monitoring of instrumented spinal surgeries that were performed for chronic underlying neurologic and neuromuscular conditions, such as scoliosis, myelopathy and spinal stenosis. We analyzed multiple montages at the baseline, and then followed their development throughout the procedure. Our intention was to examine the stability of the SEP recordings throughout the surgical procedure on multiple montages of cortical SEP recordings, with the goal of identifying the appropriate combination of the least number of montages that gives the highest yield of monitorable surgeries. Our study shows that it is necessary to have multiple montages for SEP recordings, as it reduces the number of non-monitorable cases, improves IOM reliability, and therefore could reduce false positives warnings to the surgeons. Out of all the typical montages available for use, our study has shown that the recording montage Cz-C4/Cz-C3 (Cz-Cc) is the most reliable and stable throughout the procedure and should be the preferred montage followed throughout the surgery.